Professional behaviour of teacher facilitator: Roles, beliefs and challenges - Erens, Ralf; Leuders, Timo (LUMAT-B: International Journal on Math, Science and Technology Education, 2024)
Professional development (PD) courses are developed by researchers and PD designers who are very often not the persons who conduct the PD course (Borko et al., 2014). The facilitating of teacher educators is commonly the means of scaling up PD courses to in-service teachers. Therefore, the professionalization of in-service facilitators is a goal-directed intervention to promote facilitators´ learning and their development of knowledge, as the facilitators’ realizations vary according to their professional views and beliefs relating to both, PD programs and teaching practice. However, little empirical insights exist about facilitators´ roles as educators and their beliefs. This contribution presents some empirical results concerning the way facilitators perceive their role in the process of adapting the contents in the implementation of a PD program for in-service teachers. The goal of this study was to explore the role of the facilitator, based on the underlying and connected beliefs that were reconstructed.